EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN ICT (Information, Communication and Technology) terhadap Peningkatan Profesionalisme Guru Al-Qur’an Hadits di MTs Nasyiatus Syubban Tobungan Galis Pamekasan - Syaiful Anam; Mohammad Fahrur Rozi; Idon Joni (Fakultas Agama Islam Universitas Islam Madura, 2023)
This study aims to determine the impact of the application of the ICT Learning Model as well as to determine the supporting and inhibiting factors as well as the benefits of the Application of the ICT Learning Model on the professionalism of the Teachers of the Al-Qur'an Hadith subject at MTs Nasyaiatus Syubban Tobungan Galis Pamekasan. The approach used in this study is a descriptive qualitative approach. Data sources were obtained through interviews, observations, documentation and questionnaires. while the informants to obtain research data were Al-Qur'an Hadith teachers and MTs Nasyiatus Syubban students. The results of the study show that the application of the ICT learning model has a significant and quite effective impact on the professionalism of Al-Qur'an Hadith Teachers at MTs Nasyaiatus Syubban, as evidenced by the supporting factors the learning atmosphere is more lively, students' learning motivation increases, students feel comfortable and happy, because the teacher applies the media in the learning process. While the inhibiting factor is the lack of variations in learning methods and strategies applied by Al-Qur'an Hadith teachers. The benefits of the professionalism of Al-Qur'an Hadith Teachers in learning activities can increase student motivation and enthusiasm for learning, and are able to provide patterns and colors for religious life in schools.